Effectiveness of Metacognitive Regulation Intervention on Attention-Deficit–Hyperactivity Disorder Students’ Scientific Ability and Motivation - Zheng, Haoyuan; Dong, Yang; Sun, YuanKe; Yang, Jie; Yuan, Chongbo; Wang, JinDao; Dong, Weiyang (Frontiers in Psychology, 2021)
This study investigated the effect of metacognitive regulation (McR) intervention on attention-deficit–hyperactivity disorder (ADHD) students’ astronomy knowledge acquisition and learning motivation. Through a cognitive-behavioural treatment design, this study selected 97 ADHD learners who had poor academic performance. This study divided ADHD students randomly into one experimental group and one control group. After 15 weeks of intervention, results showed that the experimental group students performed significantly better than the control group in scientific abilities, learning motivation, and metacognition. Results suggested that the McR intervention is an effective approach for improving the ADHD students’ science knowledge learning abilities.